2004
DOI: 10.1111/j.1365-263x.2004.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aspects of children's oral‐health‐related quality of life following dental treatment under general anaesthesia

Abstract: Treating young children with high disease experience in a single session under GA results in immediate improvement in oral health and aspects of their QoL for both the children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
86
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 2 publications
14
86
1
4
Order By: Relevance
“…[4][5][6][7][8][9][10] A review of the possible effects of dental caries on failure to thrive (FTT) showed that in otherwise healthy children, severe dental decay could contribute to FTT. 11 The impact of comprehensive dental intervention affected patients with both organic and non-organic FTT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] A review of the possible effects of dental caries on failure to thrive (FTT) showed that in otherwise healthy children, severe dental decay could contribute to FTT. 11 The impact of comprehensive dental intervention affected patients with both organic and non-organic FTT.…”
mentioning
confidence: 99%
“…3,4 Dental treatment makes a very significant difference to the psychological and social aspects of the child's life. 9,10,13,15,19 These improvements include less pain and improved abilities to eat and sleep. In one study, parents perceived treatment had positive social impacts on their child: more smiling, improved school performance and increased social interaction.…”
mentioning
confidence: 99%
“…In previous studies, oral intake was improved from the preoperative status at one week following dental rehabilitation. 17 Our patients were not followed after 24 hr, but we expect oral intake to have improved after this time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Os efeitos negativos da cárie dentária sobre a vida das crianças incluem: dificuldade de mastigar, diminuição do apetite, perda de peso, dificuldade para dormir, alteração no comportamento (irritabilidade e baixa auto-estima) e diminuição do rendimento escolar 5,6,7,8,9,10 . Foi relatado ainda que, quando uma criança apresenta um quadro de cárie rampante na primeira infância, o bemestar da família pode ser comprometido: os pais sentem-se culpados, e, por vezes, precisam faltar ao trabalho e ter despesas com o tratamento odontológico da criança 11 .…”
Section: Introductionunclassified